IMPACT OF INTERNATIONAL HUMANITARIAN LAW ON THE SYSTEM OF NATIONAL LEGISLATION - Boiko, Vladyslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to reveal the theoretical and legal foundations of international humanitarian law (IHL), its influence on national legislation, identify existing problems and determine the optimal ways to solve them. Discussion: it is noted that based on a systematic and comprehensive study of the concept and essence of IHL, the differentiation of approaches to understanding and interpreting this phenomenon, a separate branch of the system of modern international law, is justified, primarily in educational and scientific, encyclopedic and dictionary-reference publications. Various, sometimes significantly different definitions largely determine the adjustment of the subject of regulation, object-subject composition, source basis, etc. There are trends of convergence of IHL and various branches of national law and legislation of Ukraine, namely constitutional, defense and security, military, administrative, criminal, environmental, etc. It is also natural that IHL has an active influence and interconnection with other branches of international law (international security law, international treaty law, international organization law, international environmental law, international maritime law, international air law, international human rights law, international criminal law, etc.). Of primary theoretical and practical importance in this context is the study of the relationship between international law and national law, international universal and regional, national legal orders, their interaction and mutual influence, the implementation of international legal obligations, standards, norms and principles of IHL, including theoretical, comparative law, sectoral and applied aspects. It is necessary to single out existing problems, namely: significant obsolescence, gaps and ineffectiveness of the action of IHL, lack of proper monitoring of its implementation, different approaches, sometimes arbitrary, at one’s own discretion or patchy implementation of the norms and principles of IHL by individual states, including the aggressor state Russia. Results: the need for modernization, that is, updating and supplementing the existing provisions of IHL, mechanisms for their implementation at the international and national levels, has been identified. An interesting announced initiative – the Platform for the Progressive Development of International Humanitarian Law – can be considered as the result of mutual influence, interaction between IHL and the system of national legislation, other components of the national legal system, with the participation of a wide range of participants and in order to update IHL, increase the efficiency of implementation mechanisms, monitoring and ensuring compliance with the norms and principles of IHL, improve national legislation and law enforcement, restore peace, security and justice.